(untitled) (International Journal of Physiotherapy, 2025)
Background: A Multidisciplinary health care team refers to a group of health professionals who collaborate for a particular patient population. However, there is little information on its implementation in Saudi Arabia. This study assessed physiotherapists’ attitudes and perceptions of the multidisciplinary team (MDT) approach to musculoskeletal rehabilitation. Methods: A total of 374 physiotherapists who have at least one year of experience participated in this cross-sectional study. The Attitude Toward Health Care Team Scale, consisting of 14 items, was used to assess their attitudes toward MDT. The responses were scored on a five-point Likert scale ranging from one (strongly disagree) to five (strongly agree). Results: There was no significant association between attitude toward the MDT approach and gender, age, or years of clinical practice (p=0.124, 0.825, 0.734, respectively). There was a significant association between attitude toward the MDT and the highest level of physiotherapy degree (p= 0.002). There was no significant association between attitude toward MDT and the number of working days/week or the nature of cases handled/day (p=0.680, 0.580, respectively). There was a significant association between attitude toward the MDT and the workplace, region, number of working hours/day, and number of cases handled/day (p=0.000, 0.010, 0.000, 0.003, respectively). Conclusion: The Saudi physiotherapists had a positive attitude toward the MDT approach in musculoskeletal rehabilitation, especially the senior physiotherapists, who were more positive. Moreover, working 7-9 hours/day and handling only 4-6 cases/day, yet maintaining a positive attitude toward the MDT approach.